última mirada. - Azara, Pedro; Catalá, Magda; Frontisi-Ducroux, Françoise; Molins i Nubiola, Miquel; Trias, Eugenio; Wunenburger, Jean-Jacques; MACBA (Museu d'Art Contemporani de Barcelona), Barcelona (Barcelona : MACBA (Museu d'Art Contemporani de Barcelona), 1997)
Artaud, Antonin ; Bacon, Francis ; Beckmann, Max ; Bonnard, Pierre ; Giacometti, Alberto ; González, Julio ; Kokoschka, Oskar ; Kollwitz, Kathe ; Matisse, Henri ; Munch, Edvard ; Nolde, Emil ; Picasso, Pablo ; Schönberg, Arnold ; Torres Garcia, Joaquin
algemene bibliog. p. 75
geboortedata, tent., bibliog. per kunstenaar
Catalaans
Engels
Spaans
L'última mirada / The Last Gaze, MACBA (Museu d'Art Contemporani de Barcelona), 16.10.1997- 6.01.1998